Carbon Border Adjustment and Other Trade Policy Approaches for Climate Protection - Galina Kolev (Intereconomics, 2021)
The idea of a carbon border adjustment mechanism (CBAM) is crucial to level the playing field between domestic producers and foreign suppliers of carbon-intensive products.
Keywords: 330